Contagion and interdependence: measuring CEE banking sector co-movements - Terhi Jokipii; Brian Lucey (Bank of Finland, 2006)
Making use of ten years of daily data, this paper examines whether banking sector co-movements between the three largest Central and Eastern European Countries (CEECs) can be attributed to contagion or to interdependence. Our tests based on simple unadjusted correlation analysis uncover evidence of contagion between all pairs of countries. Adjusting for market volatility during turmoil, however, produces different results. We then find contagion from the Czech Republic to Hungary during this time, but all other cross-market co-movements are rather attributable rather to strong cross-market linkages. In addition, we construct a set of dummy variables to try to capture the impact of macroeconomic news on these markets. Controlling for own-country fundamentals, we discover that the correlations diminish between the Czech Republic and Poland, but that coefficients for all pairs remain substantial and significant. Finally, we address the problem of simultaneous equations, omitted variables and heteroskedasticity, and adjust our data accordingly. We confirm our previous findings. Our tests provide evidence in favour of parameter instability, again signifying the existence of contagion arising from problems in the Czech Republic affecting Hungary during much of 1996.
URN:NBN:fi:bof-201612201542
Keywords: F30; F40; G15; 330